A thermoeconomic analysis for home air conditioning system - Hassan, Mohamad Zaki (Universiti Teknologi Malaysia, 2003)
The application of thennoeconomics to the optimization of a home air conditioning system will be presented in this paper. The method is well suited for application to thermodynamic process and exergy destruction. The exergetic efficiency of the compressor, condenser, evaporator, expansion valve and electric motor are chosen as the decision variables to be optimized. The total cost for the component system can also be calculated